1993
DOI: 10.1002/dvg.1020140208
|View full text |Cite
|
Sign up to set email alerts
|

Lack of concordance between heat shock proteins and the development of tolerance to teratogen‐induced neural tube defects

Abstract: The present study was undertaken to examine the role of heat shock response in the development of tolerance and cross-tolerance in an in vivo murine model of teratogen-induced neural tube defects. The experimental paradigm designed to address this question was to utilize inbred mouse strains that differed in their sensitivity to hyperthermia and valproic acid induced neural tube defects, subjecting the dams to subteratogenic pretreatments with either heat or valproic acid at two different timepoints during dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…In the more resistant LM/Bc strain, FBP-1 expression at gestational day 8:18 actually increases following the valproic acid treatment (Table II) to levels which were similar to those observed in the SWV embryos. Previously, our laboratory has shown that the SWV embryos lag behind the LM/Bc in their progression through neural tube closure [Finnell et al, 1993;Wlodarczyk et al, 1996;Finnell and Bennett, unpublished]. Therefore, it is quite possible that by gestational day 8:18, the LM/ Bc embryos had progressed to a stage of neural tube development which was immune to the slight perturbations in folate transport gene expression induced by valproic acid treatment.…”
Section: Discussionmentioning
confidence: 92%
“…In the more resistant LM/Bc strain, FBP-1 expression at gestational day 8:18 actually increases following the valproic acid treatment (Table II) to levels which were similar to those observed in the SWV embryos. Previously, our laboratory has shown that the SWV embryos lag behind the LM/Bc in their progression through neural tube closure [Finnell et al, 1993;Wlodarczyk et al, 1996;Finnell and Bennett, unpublished]. Therefore, it is quite possible that by gestational day 8:18, the LM/ Bc embryos had progressed to a stage of neural tube development which was immune to the slight perturbations in folate transport gene expression induced by valproic acid treatment.…”
Section: Discussionmentioning
confidence: 92%
“…Likewise, it was shown that both resistant and susceptible strains to valproic acid-induced neural tube defects were protected by a prior 10-min 411C hyperthermia pretreatment (Finnell et al, 1993). However, in these two latter studies correlation between the induction of the heat-shock response and the thermoprotection to either cadmium or valproic acid was not specifically determined (Kapron-Bras and Hales, 1992;Finnell et al, 1993). Therefore, it appears that the heatshock response is a protective cellular mechanism that can be induced by numerous stresses.…”
Section: Mechanistic Observationsmentioning
confidence: 93%
“…Expanding this study to include both a susceptible (BALB/c) and resistant (SWV) mouse strain, it was demonstrated that the heat-pretreatment failed to significantly reduce the effects of cadmium on BALB/c embryos but did protect SWV embryos (Kapron-Bras and Hales, 1992). Likewise, it was shown that both resistant and susceptible strains to valproic acid-induced neural tube defects were protected by a prior 10-min 411C hyperthermia pretreatment (Finnell et al, 1993). However, in these two latter studies correlation between the induction of the heat-shock response and the thermoprotection to either cadmium or valproic acid was not specifically determined (Kapron-Bras and Hales, 1992;Finnell et al, 1993).…”
Section: Mechanistic Observationsmentioning
confidence: 94%
See 1 more Smart Citation
“…Although the association between maternal hyperthermia exposure and NTDs in humans remains controversial, the wealth of literature supporting its teratogenicity in animals suggests that humans would, in all likelihood, respond similarly [Finnell et al, 1993]. In fact, a number of prospective and retrospective studies support a teratogenic association in humans [Miller et al, 1978;Milunsky et al, 1992;McDonald, 1958McDonald, , 1961Coffey and Jessop, 1959;Erickson, 1991;Fraser and Skeleton, 1978;Spragett and Fraser, 1982].…”
Section: Introductionmentioning
confidence: 96%